Polychrome sculptures in Romeo and Juliet and The Winter’s Tale - Olivia COULOMB (E-REA)
Since the Reformation, English onlookers have been used to unadorned, unpainted sculptures. However, in The Winter’s Tale, Shakespeare structures the plot around Hermione’s painted statue. Its lifelike appearance serves to enlighten King Leontes about his former tragic errors. Interestingly enough, in Romeo and Juliet, the playwright had already presented the supposedly ‘deadlike’ Juliet as a recumbent statue. So, these two plays may be regarded as part of a diptych as far as the dramatic and aesthetic function of the statue-like female character is concerned. In their reactions when confronted with the coloured “statues” of their beloved, Romeo and Leontes indeed raise several questions as to the role played by the work of art.This article, will first focus on the ambivalence of colour in early modern England so as to analyze the significance of polychrome statues, before turning to the ‘statue scenes’ in both plays in order to highlight their various functions. Finally, I will argue that Romeo and Juliet and The Winter’s Tale should be understood against a complex artistic background, at a time when English artists borrowed their styles from continental and more specifically from Italian sculptures in order to refashion England’s identity.